Economic Evaluation of Nigerian Marginal Oil and Gas Field using Financial Simulation Analysis - Akinwale, Yusuf Opeyemi; Akinbami, John-Felix Kayode (International Journal of Energy Economics and Policy, 2016)
Marginal oil and gas field could contribute immensely to wealth creation, employment generation and confidence in local oil firms if properly exploited by the indigenous firms. Despite the laudable marginal field initiative by the Government, indigenous players still face challenges in exploiting these fields in Nigeria. This study evaluates the fiscal regime and the economic factors that could be hindering oil field development among the indigenous oil firms. The result of the financial cash flow modelling found that the marginal oil field's project is viable with post-tax Net Present Value (NPV) and Expected Monetary Value (EMV) above $29 million. The petroleum profit tax, royalty and crude oil price have more impacts on the field's NPV. The study suggests a periodic assessment of the fiscal regime and appropriate policy by the government to encourage the local players in developing the marginal oil field. Keywords: indigenous, marginal oil and gas field, Financial Simulation, government JEL Classifications: F38, Q47